Fiqhu al bu'd al iqtishadi li azimati al'alamin al mu'ashirah muqaddimatani manhajitani - Ali Abd Al-Mun'im Al-Mishri (Millah: Journal of Religious Studies, 2008)
The contemporary crisis of global financial, then economic, systems usually analyzed, interpreted, and perceived to be solved based on variables from within these two systems. In such frame of thinking financial assets and leverage, mortgage crisis, stock markets, etc are proposed to interpret the crisis, leaving behind many other vital variables. Vital variables are those of epistemological, axiological and ontological systems that form and guide the financial and economic actors in capitalist-globalized system. Through two methodological introductions, this article, this article proposes the contemporary crisis as an aspect named ‘economic’ of another deeper, more influential, and circumambient; which the article named "Contemporary Crisis". Al-‘aalamin in the first introduction, the article suggests that those 'economic actors’ are simply men and women, who live complex and multi-dimensional gross story. Such complex gross story cannot be dealt with (analyzed, interpreted and solved) except through a complex model (Fiqh), which budges 'economy’ from the center of humanity experience that live a dialectic (and many times conflicts) among its various elements (natural and supernatural) heading to perfectibility, even will not achieve it absolutely. Whereas in the second introduction, the article suggests a writing framework on the subject, which embodies the complex and multi-dimensional model mentioned.